Educational Implications of VARK Learning Styles: Academic Performance and Pedagogical Preferences among Korean Pharmacy Students - Lee, Sunmin (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Understanding and adapting instruction to pharmacy students' learning styles can catalyze educational outcomes, fostering the transition from knowledge acquisition to actionable skills. We investigated the learning styles of pharmacy students using the VARK model and explored their preferences for instructional methods before developing a preceptorship curriculum. Materials and Methods Our study employed a descriptive questionnaire-based approach involving pharmacy students from S City, Korea, spanning from fourth-year undergraduates to graduates. Participants underwent evaluation using the VARK test (version 7.0) to ascertain their preferred learning modalities, which encompassed Visual (V), Aural (A), Read/ write (R) and Kinesthetic (K) tasks. A total of 57 responses were collected from the 127 distributed questionnaires, yielding a response rate of 44.8%. Results The findings revealed that most students (94.7%) utilized all four learning modalities, with 'Read/Write' being the most prevalent. Significantly more males than females preferred the 'Visual' styles. However, no significant correlations were observed between learning style and students' academic performance or graduation status. Most students indicated a preference for instructor-led face-to-face teaching over online methods, with no notable differences in learning preferences among the various VARK modalities. While the VARK model aids in identifying student preferences, it does not exert a significant influence on academic outcomes or pedagogical preferences. Conclusion These results underscore the necessity for teaching strategies to be adaptable to educational content rather than strictly adhering to students’ learning style preferences.
Keywords: Learning Style; Educational Measurement; Teaching; Academic Performance; Educational Status.